Deconstructing post-exertional malaise: An exploratory factor analysis - McManimen, Stephanie L. (J Health Psychol, 2016)
Post-exertional malaise (PEM) is a cardinal symptom of myalgic encephalomyelitis (ME) and chronic fatigue syndrome (CFS). There are two differing focuses when defining PEM: a generalized, full-body fatigue and a muscle-specific fatigue. This study aimed to discern whether PEM is a unified construct or if it is composed of two smaller constructs, muscle fatigue and generalized fatigue. An exploratory factor analysis was conducted on several symptoms that assess PEM. The results suggest that PEM is composed of two empirically different experiences, one for generalized fatigue and one for muscle-specific fatigue.